Simultaneous Quantification of Pioglitazone and Omarigliptin in Rat Plasma by UHPLC-MS/MS and Its Application to Pharmacokinetic Study after Coadministration of the Two Drugs - Lin Wang; Jiaxi Wang; Chao Lin; Furong Wang; Xiangping Li; Wanhui Liu (Journal of Analytical Methods in Chemistry)
Combination therapy is a common approach for clinical treatment of type 2 diabetes mellitus, especially for patients with poor monotherapy. Meta-analysis suggested that omarigliptin, a long-acting DPP-4 inhibitor, combined with pioglitazone might improve the side effects of pioglitazone. However, little is known about the pharmacokinetic properties after a coadministration. In this study, a rapid and reliable method for the simultaneous determination of the pioglitazone and omarigliptin in rat plasma by UHPLC-MS/MS was established and validated for the first time. An exsil mono C18 column (2.0 × 50 mm, 3 μm) was used to separate the analytes and the column temperature was kept at 30°C. Sitagliptin was selected as the internal standard. 0.02% formic acid aqueous solution (A) and methanol-acetonitrile (B) were used as mobile phases with gradient elution at a flow rate of 0.3 mL/min. The elution procedure was as follows: 20%B (0–0.1 min), 80%B (0.1–0.3 min), 80%B (0.3–2.0 min), and 20%B (2.1–3.0 min). A multiple reaction monitor (MRM) was used under positive ionization mode with electrospray ion source to detect pioglitazone (357.1 ⟶ 134.1), omarigliptin (399.2 ⟶ 153.0), and sitagliptin (408.2 ⟶ 235.0). The linear ranges of pioglitazone and omarigliptin were 5–2000 ng/mL and 10–4000 ng/mL, respectively. Good linear relationships were exhibited in the corresponding linear ranges (r ≥ 0.9944). The bioanalytical method was validated, and the selectivity, linearity, sensitivity, accuracy, precision, stability, recovery, and matrix effect were acceptable. The validated method was then successfully applied to pharmacokinetic study of pioglitazone combined with omarigliptin in rats. Results suggested that the combination of the two drugs had little effect on the pharmacokinetic parameters of each other in rats.